Neratinib-Induced Duodenal Ulcer: A Case Report. (June 2020) - Moftakhar, Bahar; Kharel, Prakash; Niraula, Sujan; Gandhi, Shipra; Falkson, Carla; Dhakal, Ajay
We report a case of a 37-year-old woman who developed a duodenal ulcer while receiving adjuvant neratinib for HER2 positive breast cancer. The clinical course of abdominal pain was strongly correlated with the use of neratinib. An esophagogastroduodenoscopy (EGD) was performed and confirmed the diagnosis of a large duodenal ulcer. Neratinib was stopped, and the patient was treated with a proton pump inhibitor. Repeat EGD performed 3 months later showed complete resolution of the duodenal ulcer. Given this unexpected serious adverse event and only modest benefit of neratinib in the adjuvant setting, the decision was made to forgo further treatment with neratinib. Physicians should be aware of the gastrointestinal (GI) side effects associated with neratinib and recognize that peptic ulcer disease may be another GI toxicity associated with neratinib use.